Colonialism and Development in the Contemporary World - Edited by Chris Dixon and Michael Heffernan (London Mansell Publishing Ltd., 1991)
A collection of essays examining the various ways in which 19th and 20th century European rule has affected the economic, social and political geography of post-colonial countries. A series of richly textured, local studies conveying the nature of colonial experience and examining in detail the key issues in the debate about the nature of imperialism. Although each chapter stands alone as an independent statement with its own focus and conclusions, they all address the central theme and provide a comparative analysis of similar processes.
Include Index,Illustrations and Maps.
Keywords: Europe -- Colonies -- Africa -- History. -- Colonies -- Africa -- History